Optimizing the placement and content of burnable poison in Gama-Float reactor’s fuel assembly - Prasetyo, Daniel A.; Agung, Alexander; Sihana, Sihana (Asia-Pacific Journal of Science and Technology, 2024)
Floating Nuclear Power Plant (FNPP) is used to potentially fulfil the energy needs of a remote region. In this context, a new FNPP reactor named Gama-Float was designed to tackle different issues. The first stage of the design process was producing a fuel assembly design without burnable poison. However, the design was inadequate at beginning-of-cycle (BOC) since multiplication factor (k∞) was relatively high and required compensation. Therefore, this research aimed to develop an optimization process using the Method of Characteristics for neutronic calculations in achieving a better design based on a genetic algorithm. The results showed that optimization must satisfy two objectives, namely lowering the multiplication factor and maintaining the fuel cycle length. A subsequent analysis was carried out to select results from the optimization. In this context, the assemblies’ initial multiplication factor, fuel cycle length, and power peaking factor (PPF) were analyzed and the final design was selected based on the analysis. The initial multiplication factor and fuel cycle were reduced to 1.0054 and 3644.41 days, while the radial PPF increased to 1.2789 at BOC in an acceptable range. These results highlight the effectiveness of the optimization process in improving neutronic performance and fuel cycle efficiency for the Gama-Float reactor.